DEMOCRACY AND AUTONOMY TRANSFORMATION IN THE GOVERNANCE OF MENGWI VILLAGE IN THE TRANSITION ERA: A CULTURAL STUDIES PERSPECTIVE - Suacana, I Wayan Gede; Paramartha, I Gde; Yudha Triguna, Ida Bagus Gde; Pasek Diantha, Made (E-Journal of Cultural Studies; Vol. 3, No. 2 Juli 2009, 2012)
This study discusses “Democra cy and Autonomy Transformation in theGovernance of Mengwi Village in the Transition Era: A Cultural StudiesPerspective”. The problem investigated was the shift in the nation’s approach to thepolicy of villages after the reign of New Order. In this era, the policy ofdemocratization and decentralization appeared till the village level. However, thepolicy was not totally implemented in the villages. The aims of this study are: todescribe democracy transformation in the village governance in the transition era, toclarify autonomy transformation in the village governance in the transition era, and toanalyze the implication and the sense of democracy and autonomy transfor mation tothe development of village governance.This study was conducted employing qualitative method. Various forms ofdemocracy and autonomy transformation in the village governance took place duringthe transition era. In the first stage, the primary and secondary data were collected. Inthe second stage, the theory applied for examining the data was chosen, and in thethird stage, the collected and classified data were analyzed and interpreted. In thefourth stage the results of the study were reported and constructed. The theoriesapplied in this study include; democracy, political democracy, substantial democracy,decentrali zation and political culture. The approaches applied were Tranpolitic andpost-structuralism.The results of the study showed that; first, the village democracy in the firsttransition era (1998-1999) was mostly still uniform, and there were not many choicesin the implementation of the village democracy. The village autonomy was stillblocked in centralistic pattern, homogeneous with hierarchical structure. Second, inthe second transition era (2000-2004) the role of the village representatives became sodemocratic accompanied by the extended village autonomy. Third, in the thirdtransition era (2005-2008) democracy became retransformed to the procedural patternaccompanied by the strengthening of supra village government power decreasing theautonomy of the villages. Fourth, democracy and autonomy transformationcontributed to the demand for the strengthening of democracy institutions, bettercommunity participation and more accountable public services, transparence and responsiveness to what was needed by the people. Fifth, democracy and villageautonomy transformation, in addition to having the sense of involving the activeparticipation of the society in the village governance, also had the sense ofstrengthening the civil and political society in every village social organization whichactualized what was needed by the society. This condition at the same timefunctioned as the responses to nation’s hegemony through the supra villagegovernment which took place until the first transition era.
Keywords: democracy and autonomy transformation, supra village power relation, dynamic of village governance, cultural studies.